Optical tomography : real-time image reconstruction for various flow regime in gravity flow conveyors - Abd. Rahim, Ruzairi; Pang, Jon-Fea; Chan, Kok San; Leong, Lai Chean; Rahiman, Mohd. Hafiz Fazalul (Akademik Sains Malaysia, 2007)

(untitled)
In this study, real-time imaging was monitored for flowing solid particles when various baffles were created to block certain areas of the pipe. The generated flow regimes were full-flow, three-quarter-flow, half-flow and quarter-flow. A vertical pneumatic conveyor was designed to hold a 85 mm inner diameter pipeline. The four projection optical tomography systems used, applied the parallel beam projection approach and use infrared light sources so that the sensor was free of noise from the surrounding visible light source. The two orthogonal and two rectilinear projections were axial, but ideally they should have been in the same layer. The sensor readings could be related to the varying light intensity effects of the dropping particles and were used to provide cross-sectional distribution information for the conveyor. By using computer programming, the information was reconstructed to produce coloured images and concentration was obtained by reference to a colour code. The results obtained from this study showed how imaged flow followed the artificial flow regime. This study could benefit industrial production lines in maintaining the desired flow rates.